The Use of Psychoactive Substances in Al-Jouf Region: Prevention and Treatment - Al-Otaibi, Dhaifallah bin Muqhim; Suleiman, Hany Fouad Sayed Mohamed (Journal of Posthumanism, 2025)
The current study aimed to examine the abuse of psychoactive substances in the Al-Jouf region and to identify the psychological and social indicators of psychoactive substance abuse, along with prevention and treatment strategies. The objective is to develop practical preventive and therapeutic plans and programs to help reduce the spread of psychoactive substance abuse in the Al-Jouf region. The study employed the following material: a diagnostic interview (closed–open) for substance users in treatment (developed by the researchers), a diagnostic interview (closed–open) for therapists, and an addiction indicators scale (developed by the researchers). These study materials were applied to a sample of 78 substance users receiving treatment at Mental Health Hospital, and 57 therapists. The results indicated that the most important reasons for abusing psychoactive substances are: certain psychological variables such as impulsivity, psychological sensitivity, depression, anxiety, inability to communicate, and social isolation, psychological fatigue, bad peers at school, in the neighborhood, or at university, low self-confidence, attempts to feel self-worth and self-esteem, lack of hobbies or skills, leisure time and attempts to fill it, Improper reactionary behavior from the family of the abuser, family problems and feelings of fragmentation and domestic abuse, parental separation, lack of guidance, counseling and mentoring inside the family, presence of a substance abuser within the family, the wide spread of substance misuse in the user’s residential area, academic failure and lack of supervision at school or university, lastly, either the abundance of income (making it easier to access substances).